Estratégias genéricas e estilos cognitivos : um estudo descritivo das empresas do setor do vestuário de Londrina - Ribas, Carlos Alberto (2007)
The purpose of the research was to describe the generic strategies and the cognitive styles, present in the companies Management in the clothing sector of Londrina County. There is not until now a study that approaches this topic. The methodological methods included: a) review the literature on strategies, cognitive styles and clothing sector; b) primary data collecting to characterize the managers of the companies in the clothing sector of Londrina; c) classification of the companies in the sector within the four theoretical categories of the generic strategies of Miles and Snow (1978); d) classification of the cognitive styles of the company managers of the sector according to the typology of Kirton (1976). The field research that allowed the primary data collecting was developed according to a questionnaire answered by 30 managers. The questionnaire developed from the researched concepts in the literature review contains three answer sections. We have verified that there are fifteen companies that have characteristics of analytical companies, tem prospective, three defensive and two reactive, in an expected outcome. The managers' frequency (86%) with punctuation between 80 and 112 points overcame the expected (67%). We did not find any manager with characteristics of extreme adapter. There were four managers who fit as extreme innovators. The correlation rate found in the main variables, strategy and style, was 0,129, considered a light association force, almost unnoticeable.